Kinetic Study of the Hydrophobic Modified-ZnO Kapok using Pseudo First Order and Pseudo Second Order Model for Cooking Oil Adsorption - M. A. Bukhori Hamidon,; Rosniza Hussin,; Zawati Harun,; Muhamad Zaini Yunos,; Ainun Rahmahwati Ainuddin@Nordin,; Clement Pakiam,; M. K. Azuan,; U. S. Nabilah, (International Journal of Integrated Engineering, 2025)
This study investigates the kinetic behaviour of hydrophobic modified-ZnO kapok fibers for the adsorption of used cooking oil. The modification of natural kapok fibers with ZnO nanoparticles was achieved using a hydrothermal process, enhancing their hydrophobic and oleophilic properties. The adsorption kinetics were evaluated using pseudo-first-order (PFO) and pseudo-second-order (PSO) models to describe the oil sorption behaviour of raw kapok fibers (RKF) and modified kapok fibers (MKF). The study revealed that MKF (114.7 g/g) exhibited higher oil adsorption capacity than RKF (88.6 g/g) after 30 minutes adsorption period, with the PSO model providing a better fit for the experimental data by showing R2 value close to 1 for both RKF (R2 = 0.9942) and MKF (R2 = 0.9781) sample. The results suggest that the modification of kapok fibers with ZnO significantly improves their oil adsorption capacity, making them a viable and eco-friendly alternative for oil spill remediation.